2019
DOI: 10.4103/1735-5362.251853
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene increases Fas expression in T-lymphoblastic leukemia cell lines

Abstract: Treatment of acute lymphoblastic leukemia (ALL) has been promising in last decades, but side effects still persist and searching for the least toxic agents continue. Pterostilbene (PTE) is a natural compound with several anti-cancer and anti-oxidant properties. Fas, as a member of death inducing family of tumor necrosis factor (TNF) receptors with an intracellular death domain, can initiate the extrinsic apoptosis signaling pathway. Here after the half maximal inhibitory concentration (IC 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Fas, as a member of the death-inducing family of tumor necrosis factors (receptors with an intracellular death domain) can initiate the extrinsic apoptosis signaling pathway. [ 20 ] In the present case, Fas expression was not detected in the CD4 + ATLL, this might be associated with a reduction in the apoptosis rate and may be one of the reasons for the long-term survival of ATLL cells.…”
Section: Discussionmentioning
confidence: 53%
“…Fas, as a member of the death-inducing family of tumor necrosis factors (receptors with an intracellular death domain) can initiate the extrinsic apoptosis signaling pathway. [ 20 ] In the present case, Fas expression was not detected in the CD4 + ATLL, this might be associated with a reduction in the apoptosis rate and may be one of the reasons for the long-term survival of ATLL cells.…”
Section: Discussionmentioning
confidence: 53%
“…It was initially isolated from sandalwood, but is also present in fruits, including grapes and blueberries [ 130 ]. The pterostilbene wide range of bioactive properties comprehends antioxidant, anti-inflammatory, anticancer, and cardioprotective effects [ 131 , 132 , 133 , 134 ], which altogether may contribute to the prevention of various chronic human diseases. Moreover, it seems to improve cognitive performances [ 135 ].…”
Section: Polyphenols’ Effects In Dedmentioning
confidence: 99%
“…Fas or CD95/APO-1, a member of the superfamily of tumor necrosis factor receptors, is one of the significant molecules contributing to the extrinsic pathway of apoptosis (50). Binding apoptotic ligands to Fas receptor leads to homo-trimerization of this receptor, signaling transduction, death complex formation, and cell death (89). It is suggested that A to G substitution at the mentioned position leads to Fas dysregulation and resistance to treatment.…”
Section: Polymorphismsmentioning
confidence: 99%